Theatre and telepresence technologies: inventions, mutations and dynamics (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
The present research addresses the performative theatre creations developed in real time in the environment of the international computer network, questioning the dynamics established between scene and reception, actors/performers and spectators. Based on the recognition of the nature of the contracts between the spectator and the scene promoted by the first theatrical practices associated with teletechnologies, the study discusses the transformations brought by digital technology, highlighting the importance of the participants’ visibility markers among themselves and the possibilities of interaction of the audience with the scene as factors in the establishment of the feeling of collective experience in online creation in real time.
Keywords: Digital Performance; Virtual Theatre; Reception